Alumina supported carbon composite material with exceptionally high defluoridation property from eggshell waste - Lunge, Sneha; Thakre, Dilip; Kamble, Sanjay; Labhsetwar, Nitin K.; Rayalu, Sadhana (Journal of Hazardous Materials, 2012)
A new alumina supported carbon composite material called ``Eggshell Composite'' (EC) was synthesized from eggshell waste as calcium source for selective fluoride adsorption from water. The effect of various synthesis parameters like eggshell (ES): Eggshell membrane (ESM) ratio, aluminium loading, mixing time and calcinations temperature to optimize the synthesis conditions for selective fluoride removal has been studied. It was observed that the synthesis parameters have significant influence on development of EC and in turn on fluoride removal capacity. EC synthesized was characterized for elemental composition, morphology, functionality and textural properties. Results showed that EC obtained from eggshell modified with alumina precursor is more selective and efficient for fluoride removal. Langmuir and Freundlich isotherm were used to obtain ultimate fluoride removal capacity. The calcium and alumina species in EC shows synergistic effect in fluoride adsorption process. Fluoride sorption studies were carried out in synthetic, groundwater and wastewater. EC proved to be a potential, indigenous and economic adsorbent for fluoride removal. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Composite material; Eggshell; Eggshell membrane; Fluoride adsorption; Langmuir

Carbon dioxide capture using amine functionalized silica gel - Sakpal, Tushar; Kumar, Asheesh; Kamble, Sanjay; Kumar, Rajnish (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Commercially available silica gel is chemically modified for carbon dioxide capture. Calcinated silica gel of certain particle size functionalized with amine using two different methods, wet impregnation and grafting via silane chemistry has been employed as a porous media. The prepared material is characterized by Fourier transform infrared, scanning electron microscopy, energy dispersive analysis of X-rays, thermogravimetry and N-2 physisorption techniques. Gas uptake measurements have been carried out to ascertain the CO2 capture capacity of the amine functionalized material. The experiments have been carried out at moderate pressure and temperature range to ascertain its potential for easy scale up.
Keywords: Amine functionalized silica gel; Carbon dioxide capture; grafting; Poly(ethyleneimine); Silane chemistry; Wet impregnation

Chitosan-based lead ion-imprinted interpenetrating polymer network by simultaneous polymerization for selective extraction of lead(ii) - Hande, Pankaj E.; Kamble, Sanjay; Samui, Asit B.; Kulkarni, Prashant S. (Industrial & Engineering Chemistry Research, 2016)
In this study, we report the synthesis of a Pb(II) ion-imprinted interpenetrating polymer network (II-IPN) by simultaneous polymerization for selective extraction of Pb(II) from printed-circuit-board (PCB) recycling unit wastewater. Initially, a polymer network was synthesized by polymerization of methacrylic acid (monomer) and ethylene glycol dimethacrylate (cross-linker) and a second polymer network by chitosan (complexing monomer) and tetraethyl orthosilicate (cross-linker). The chemical structure and morphology of the II-IPN were analyzed using Fourier transform infrared, field-emission scanning electron microscopy, atomic force microscopy, and transmission electron microscopy. The interaction of the functionality in the II-IPN with Pb(II) through chelation was studied by X-ray photoelectron spectroscopy analysis. The maximum adsorption capacities for II-IPN and nonimprinted interpenetrating polymer network were 37.5 and 10.3 mg g(-1), respectively. The largest selectivity coefficient for Pb(II) in the presence of W(VI) was 161.58. The developed Pb(II) II-IPN was successfully employed for selective extraction of Pb(II) from PCB recycling unit wastewater.

Exploiting phosphate-starved cells of scenedesmus SP for the treatment of raw sewage - Yewalkar-Kulkarni, Swati; Gera, Gayatri; Nene, Sanjay; Pandare, Kiran; Kulkarni, Bhaskar; Kamble, Sanjay (Indian Journal of Microbiology, 2017)
Phosphate depletion is one of the favorable ways to enhance the sewage water treatment with the algae, however, detailed information is essential with respect to internal phosphate concentration and physiology of the algae. The growth rate of the phosphate-starved Scenedesmus cells was reduced drastically after 48 h. Indicating cells entered in the stationary phase of the growth cycle. Fourier Transform Infrared analysis of phosphate-starved Scenedesmus cells showed the reduction in internal phosphate concentration and an increase in carbohydrate/phosphate and carbohydrate/lipid ratio. The phosphate-starved Scenedesmus cells, with an initial cell density of, 1 x 10(6) cells mL(-1) shows 87% phosphate and 100 % nitrogen removal in 24 h. The normal Scenedesmus cells need approximately 48 h to trim down the nutrients from wastewater up to this extent. Other microalgae, Ankistrodesmus, growth pattern was not affected due to phosphate starvation. The cells of Ankistrodesmus was able to reduce 71% phosphate and 73% nitrogen within 24 h, with an initial cell density of, 1 x 10(6) cells mL(-1).
Keywords: Ankistrodesmus; Fourier Transform Infrared; Phosphate starvation; Scenedesmus; Sewage treatment

Two-step sequence of acetalization and hydrogenation for synthesis of diesel fuel additives from furfural and diols. - Patil, Anil; Shinde, Suhas; Kamble, Sanjay; Rode, Chandrashekhar, V (Energy & Fuels, 2019)
Acetalization of diols with furfural and subsequent hydrogenation of acetal products provided potential fuel additives that could be blended into commercial diesel. Glycerol could be an interesting polyol for acetalization with furfural due to its low cost, and it is produced as a byproduct in very large amount in the process of biodiesel production. In this work, glycerol acetalization with furfural has been selected as a model reaction. Acetalization reaction was performed under neat conditions (solventless) with 1:1 molar ratio of furfural and glycerol at room temperature over various acid catalysts, including homogeneous and heterogeneous acids. Among several catalysts, Zr-Mont, a heterogeneous solid acid having controlled acidity, gave as high as 78% isolated yield of acetal products. Interestingly, acetal products can be isolated in pure form by performing extraction using cyclohexane that enables selective extraction of product, and unreacted glycerol and furfural were left in aqueous phase, which can be recycled. Further, to make fuel components from isolated acetal product of glycerol and furfural, hydrogenation was performed over a series of supported noble-metal catalysts under low H-2 pressure at room temperature. Among them, 5% Pd/C showed very high activity for ring hydrogenation that resulted in high yield of hydrogenation products. However, hydrogenated product contains free hydroxyl group that needs to be subsequently etherified or acetylated. Interestingly, etherified derivative was obtained in high yield compared to acetylated derivative. In addition, several other diols were treated with furfural and their products were subsequently hydrogenated over 5% Pd/C under very low H-2 pressure. The properties of resulting compounds were investigated so as to find most suitable candidates as additives to commercial diesel.

Metagenome sequencing to unveil microbial community composition and prevalence of antibiotic and metal resistance genes in hypersaline and hyperalkaline Lonar Lake, India - Chakraborty, Jaya; Sapkale, Vibhavari; Shah, Manan; Rajput, Vinay; Mehetre, Gajanan; Agawane, Sachin; Kamble, Sanjay; Dharne, Mahesh (Ecological Indicators, 2020)
Lonar Lake (India) is a hyperalkaline and hypersaline soda lake encompassing unique microbial composition and functions. This ecosystem has not been explored for taxonomic diversity and functional aspects (with emphasis on antibiotic and metal resistance genes) using whole metagenome sequencing for multiple years. Bacterial diversity analysis during year 2013, 2016, and 2018 depicted differences in the dominance of Proteobacteria, Firmicutes and Bacteroidetes. For archaeal diversity, a similar pattern persisted with higher abundance of Euryarchaeota. Functional metagenome analyses, indicated presence of antibiotic resistance gene (ARG) and metal resistance gene (MRG) profiles in the lake. A wider continuum of resistance genes with dominant ARG types as multidrug resistance efflux pumps and beta-lactams were also observed. The lake resistome demonstrated fluoroquinolone and acriflavine resistance genes indicating sewage water contamination in the lake. The MRGs linked with resistance to toxic metals (arsenic, cobalt, cadmium, copper, and zinc) and cation efflux protein CusA and cobalt-zinc-cadmium resistance protein revealed metal contamination. This study could be a baseline for understanding prevalence of antibiotic and metal resistance mechanisms resulting from various anthropogenic activities nearby lake, and find integrated approaches for conservation of the precious Lonar Lake ecosystem.
Keywords: Archaeal diversity; ARGs; Bacterial diversity; Illumina sequencing; Lonar lake; MRGs

Shotgun metagenome guided exploration of anthropogenically driven resistomic hotspots within Lonar soda lake of India - Chakraborty, Jaya; Sapkale, Vibhavari; Rajput, Vinay; Shah, Manan; Kamble, Sanjay; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
Anthropogenic activities mediated antibiotic resistance genes (ARGs) in the pristine aquatic bodies (lakes) is raising concern worldwide. Long read shotgun sequencing was used to assess taxonomic diversity, distribution of ARGs and metal resistance genes (MRGs) and mobile genetic elements (MGEs) in six sites within hypersaline Lonar soda lake (India) prone to various anthropogenic activities. Proteobacteria and Euryarchaeota were dominant phyla under domain Bacteria and Archaea respectively. Higher abundance of Bacteroidetes was pragmatic at sites 18LN5 and 18LN6. Functional analysis indicated 26 broad-spectrum ARGs types, not reported earlier in this ecosystem. Abundant ARG types identified were multidrug efflux, glycopepetide, bacitracin, tetracycline and aminogylcoside resistance. Sites 18LN1 and 18LN5 depicted 167 and 160 different ARGs subtypes respectively and rpoB2, bcrA, tetA(48), mupA, ompR, patA, vanR and multidrug ABC transporter genes were present in all samples. The rpoB2 gene was dominant in 18LN1, whereas bcrA gene in 18LN2-18LN6 sites. Around 24 MRGs types were detected with higher abundance of arsenic in 18LN1 and copper in 18LN2-18LN6, signifying metal contamination linked to MRGs. The bacterial taxa Pseudomonas, Thioalkalivibrio, Burkholderia, Clostridium, Paenibacillus, Bacillus and Streptomyces were significantly associated with ARGs. This study highlights the resistomic hotspots in the lake for deploying policies for conservation efforts.
Keywords: ARGs; diversity; Lonar lake; MGEs; MRGs; Nanopore sequencing

Spatio-temporal resolution of taxonomic and functional microbiome of Lonar soda lake of India reveals metabolic potential for bioremediation - Chakraborty, Jaya; Rajput, Vinay; Sapkale, Vibhavari; Kamble, Sanjay; Dharne, Mahesh (Chemosphere, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Lonar Lake, India; a hypersaline and hyperalkaline extremophilic ecosystem having a unique microbial population has been rarely explored for bioremediation aspects. MinION-based shotgun sequencing was used to comprehensively compare the microbial diversity and functional potential of xenobiotic degradation pathways with seasonal changes. Proteobacteria and Firmicutes were prevalent bacterial phyla in the pre-monsoon and post-monsoon samples. Functional analysis from SEED-subsystem and KEGG database revealed 28 subsystems and 18 metabolic pathways for the metabolism of aromatic compounds and xenobiotic biodegradation respectively. Occurrence of N-phenyl alkanoic, benzoate, biphenyl, chloroaromatic, naphthalene, and phenol degradation genes depicted varied abundance in the pre-monsoon and post-monsoon samples. Further, KEGG analysis indicated nitrotoluene degradation pathway (ko00633) abundant in post-monsoon samples, and the benzoate degradation pathway (ko00362) predominant in 19LN4S (pre-monsoon) than 18LN7S (post-monsoon) samples. The abundant genes for benzoate degradation were pcaI: 3-oxoadipate CoA-transferase, alpha subunit, pcaH: protocatechuate 3,4-dioxygenase, beta subunit, and pcaB: 3-carboxy-cis, cis-muconate cycloisomerase, and 4-oxalocrotonate tautomerase. This metagenomic study provides a unique blueprint of hitherto unexplored xenobiotic biodegradation genes/pathways in terms of seasonal variations in the Lonar Lake, and warrants active exploitation of microbes for bioremediation purposes.

Novel lignin as natural-biodegradable binder for various sectors-A review - Mili, Medha; Hashmi, Sayed Azhar Rasheed; Ather, Madeeha; Hada, Vaishnavi; Markandeya, Nishant; Kamble, Sanjay; Mohapatra, Mamata; Rathore, Sanjai Kumar Singh; Srivastava, Avanish Kumar; Verma, Sarika (Journal of Applied Polymer Science, 2022)
Lignin functions as an essential polymer in plants that forms the plant body's structural framework. The natural glue holds the cellulosic fibers together in the plant body, thereby providing rigidity and strength. Despite this, lignin shows promising relevance for biomaterial production due to its abundance, nontoxic nature and biodegradability. Considerably, adhesive components were derived from petroleum, which is increasingly more expensive. Hence, lignin, the natural glue in plant materials, gained much popularity because of its phenolic nature, making it an attractive substitute for adhesives. Lignin-based binders are produced through phenols substitution in phenol-formaldehyde resins with lignin due to their similar structural framework. Many researchers have confirmed the multifunctional applications of lignin, such as wood adhesive in fiber board, plywood and particleboard, a binder in printed wiring boards, abrasive tools, epoxy asphalts, epoxy wood composites, 3D printing, adhesive hydrogels, soil suppressants, lignocellulosic paper and coatings. This review presents a comprehensive description of the utilization of lignin-based binders for different applications. The present work highlights the discussion on the various methods by which lignin can be used to replace synthetic binders. This review focuses on global research work introducing lignin in different chemical adhesives for a more cost-effective and less harmful alternative.
Keywords: binder; biodegradable; lignin; multifunctional

Comparative evaluation of advanced oxidation processes (AOPs) for reducing SARS-CoV-2 viral load from campus sewage water - Pramanik, Rinka; Bodawar, Narendra; Brahme, Aashay; Kamble, Sanjay; Dharne, Mahesh (Journal of Environmental Chemical Engineering, 2023)
Presence of SARS-CoV-2 in wastewater is a major concern as the wastewater meets rivers and other water bodies and is used by the population for various purposes. Hence it is very important to treat sewage water in an efficient manner in order to reduce the public health risk. In the present work, various advanced oxidation processes (AOPs) have been evaluated for disinfection of SARS-CoV-2 from sewage water collected from STP inlet of academic institutional residential. The sewage water was subjected to ten AOPs, which include Ozone (O3), Hydrodynamic cavitation (HC), Ultraviolet radiation (UV), and their hybrid combinations like HC/O3, HC/O3/ H2O2, HC/H2O2, O3/UV, UV/H2O2, UV/H2O2/O3, and O3/H2O2 to reduce SARS-CoV-2 viral load. Further, AOP treated sewage water was subjected to total nucleic acid isolation followed by RT-qPCR for viral load estimation. The sewage water treatment techniques were evaluated based on their viral concentration-reducing efficiency. It was found that ozone and ozone-coupled hybrid AOPs showed the most promising result with more than 98 % SARS-CoV-2 viral load reducing efficiency from sewage water. Interestingly, the best six AOPs used in this study significantly reduced both the SARS-CoV-2 and PMMoV (faecal indicator) viral load and improved water quality in terms of increasing DO and decreasing TOC.
Keywords: AOPs and hybrid AOPs; Hydrodynamic cavitation; Ozonation; PMMoV; SARS-CoV-2; Sewage water treatment

Genomic surveillance reveals early detection and transition of delta to omicron lineages of SARS-CoV-2 variants in wastewater treatment plants of Pune, India - Rajput, Vinay; Pramanik, Rinka; Malik, Vinita; Yadav, Rakeshkumar; Samson, Rachel; Kadam, Pradnya; Bhalerao, Unnati; Tupekar, Manisha; Deshpande, Dipti; Shah, Priyanki; Shashidhara, L. S.; Boargaonkar, Radhika; et al. (Environmental Science and Pollution Research, 2023)
The COVID-19 pandemic has emphasized the urgency for rapid public health surveillance methods to detect and monitor the transmission of infectious diseases. The wastewater-based epidemiology (WBE) has emerged as a promising tool for proactive analysis and quantification of infectious pathogens within a population before clinical cases emerge. In the present study, we aimed to assess the trend and dynamics of SARS-CoV-2 variants using a longitudinal approach. Our objective included early detection and monitoring of these variants to enhance our understanding of their prevalence and potential impact. To achieve our goals, we conducted real-time quantitative polymerase chain reaction (RT-qPCR) and Illumina sequencing on 442 wastewater (WW) samples collected from 10 sewage treatment plants (STPs) in Pune city, India, spanning from November 2021 to April 2022. Our comprehensive analysis identified 426 distinct lineages representing 17 highly transmissible variants of SARS-CoV-2. Notably, fragments of Omicron variant were detected in WW samples prior to its first clinical detection in Botswana. Furthermore, we observed highly contagious sub-lineages of the Omicron variant, including BA.1 (similar to 28%), BA.1.X (1.0-72%), BA.2 (1.0-18%), BA.2.X (1.0-97.4%) BA.2.12 (0.8-0.25%), BA.2.38 (0.8-1.0%), BA.2.75 (0.01-0.02%), BA.3 (0.09-6.3%), BA.4 (0.24-0.29%), and XBB (0.01-21.83%), with varying prevalence rates. Overall, the present study demonstrated the practicality of WBE in the early detection of SARS-CoV-2 variants, which could help track future outbreaks of SARS-CoV-2. Such approaches could be implicated in monitoring infectious agents before they appear in clinical cases.
Keywords: Bioinformatics pipeline; COVID-19; Early warning; India; Next-generation sequencing; Omicron; Public health; SARS-CoV-2; wastewater; Wastewater-based epidemiology

Novel shear thickening fluids possessing high shear rates using monodispersed silica nanoparticles and PEG - Chavan, Nayaku; Dhage, Atul; Wale, Apparav; Thorave, Asmita; Rajdeo, Kishor; Kamble, Sanjay; Ponrathnam, Surendra; Tambe, Sanjeev; Verma, Sanjeevkumar (Polymer Bulletin, 2023)
Higher shear rate possessing homogeneous shear thickening fluids were synthesized using monodispersed silica nanoparticles and polyethylene glycol (PEG). Novel homogeneous methodology was developed for the synthesis of shear thickening fluids using monodispersed silica nanoparticles and PEG. Shear rate of shear thickening fluids (STF) was determined using rheometer at room temperature. The normal shear rate was observed in the range of 100 to 1200 s(-1), whereas higher shear rate 2000 s(-1) was obtained using monodispersed silica nanoparticles, PEG and shear rate enhancer. Monodispersed silica nanoparticles were synthesized in a typical one-pot using modified Stober's method at room temperature. Precursors were used for the synthesis of monodispersed silica nanoparticles such as tetraethyl orthosilicate (TEOS), ethanol, deionized water and ammonia as catalyst. Particle size of monodispersed silica nanoparticles was in the range of 100-1200 nm, and particle size distribution was varied from 0.000 to 0.221. Synthesis of monodispersed silica nanoparticles was studied by various parameters, namely effect of TEOS concentration, grade of ethyl alcohol, ammonia concentration and water concentration. TEOS concentration effect shows particle size and particle size distribution increases with increase in concentration of TEOS. Even though concentration of TEOS was increased up to 5 times the observation was same for all particle sizes such as 100, 300 and 500 nm. Particularly in the case of 300 nm monodispersed silica nanoparticle synthesis, as TEOS concentration was increased from 1 to 5X (5 times) the particle size was increased from 331.7, 447.8, 497.0, 512.0 and 531.7 nm and particle size distribution was 0.005, 0.000, 0.006, 0.007 and 0.089, respectively. The effect of grade of ethyl alcohol illustrates that Indian rectified spirit shows almost similar results with respect to China make ethyl alcohol. Comparative study of China and Indian rectified spirit shows silica nanoparticle size was 174.6 and 174.2 nm, and particle size distribution was 0.065 and 0.071, respectively. Ammonia concentration effect explains particle size and particle size distribution increases with increase in concentration of ammonia. Water concentration effect shows particle size and particle size distribution increases with increase in concentration of ammonia. Comparative data of water concentration effect for 1316 and 1974 mL shows particle size were 321.7 and 488.0 nm, and particle size distribution was 0.083 and 0.05, respectively, under similar conditions. Morphological studies displayed the shape of the silica nanoparticles was spherical, monodispersed and isolated. A typical TEM image of monodispersed silica nanoparticles for 500 nm was observed with extremely low polydispersity, i.e., 0.000. It is very difficult to get such a type of excellent photograph of monodispersity by Stober's method particularly on large scale. Rheology study of homogeneous shear thickening fluids studied by varying the parameters such as composition of silica nanoparticles with PEG, effect of amount of solvent, effect of refluxing time, effect of additive with respect to the mol. wt. of PEG and effect of additive such as Tannin. All these parameters of STF explored with respect to the shear rate and shear viscosity. Effect of ethanol amount on STF demonstrates the shear rate increases with increase in amount of solvent. Effect of refluxing time on STF exhibits the shear rate increases with increase in refluxing time. Effect of composition based on 500 nm monodispersed silica nanoparticles and PEG 200 with respect to 60:40, 65:35 and 70:30 composition was studied and the results predict that shear rate increases with increase in silica percentage in composition, i.e., 118, 265 and 1200 s(-1) for 60:40, 65:35 and 70:30 composition, respectively, whereas maximum viscosity decreases with increase in silica content, i.e., 2.559, 1.420 and 1.200 Pa.s for 60:40, 65:35 and 70:30 composition, respectively. Effect of additive on shear rate and shear viscosity illustrates that shear rate decreases with increase in additive percentage in composition, whereas maximum viscosity increases with increase in additive content. Effect of additives on shear rate and shear viscosity was performed using 65:35 composition with respect to PEG 200 along with PEG 6000 shows shear rate was decreased from 142 to 6.42 s(-1) and maximum viscosity was increased from 56.1 to 571.0 Pa.s when the quantity of PEG 6000 was doubled. In general, additive decreases shear rate and increases shear viscosity (maximum). But effect of Tannin as an additive on 500 nm monodispersed silica nanoparticles with PEG 200 using 70:30 composition showed enormous increase in shear rate, i.e., 2000 s(-1). This is anomalous behavior of additive was observed.
Keywords: Monodispersed silica nanoparticles; Nanocomposite; Polyethylene glycol; Shear rate; Shear thickening fluid

Synthesis of advanced asbestos-free material using rice husk ash and marble waste for thermal insulation applications - Verma, Sarika; Bajpai, Harsh; Suresh, S.; Mili, Medha; Gupta, Ritesh Kumar; Shetty, Rohit; Kamble, Sanjay; Khan, Mohd. Akram; Hashmi, S. A. R.; Srivastava, A. K. (Biomass Conversion and Biorefinery, 2023)
The importance and utilization of advanced thermal insulating materials increase due to their broad and irreplaceable energy conservation role. This paper describes the novel way of achieving insulating material. In two waste by-products, namely rice husk ash (RHA), agriculture waste, and marble waste powder (MWP), industrial waste has been utilized to make asbestos-free advanced material for thermal insulation. A novel method for making asbestos-free advanced material for thermal insulation using RHA and marble waste's inherent characteristics has developed mechano-chemical for appropriate physico-chemical consolidation, densification, and ceramic processing route. The Si and Ca sources undergo a series of chemical transformations accompanied by mass transfer and thermal reactions during the synthesis process. The formation of this silicate compound occurs due to the presence of higher contents of CaO in marble waste powder (MWP) and silica in rice husk ash (RHA), resulting in thermal insulating characteristics in the advanced thermal insulation material (ATIM). Raman spectra of ATIM after heating at 1100 degrees C were mainly amorphous, which had a broad peak at 1072 cm(-1). This shows thermal transformation occurs after the heating process, the admixture of tailored powder, and fly ash (FA). The density of the ATIM is found to be 1150 kg/m(3). The phase transformation (glass transition temperature) was found in all the samples between 600 and 800 degrees C. The mechanical properties, namely the compressive strength and impact strength evaluation test, showed that the material meets the standard specifications for ceramic tiles. The thermal conductivity (W/mK) was calculated from different temperature 30, 50, 100,150, and 200 degrees C and found to be 0.571, 0.541, 0.516, 0.498, and 0.477, respectively. According to the test results, it is concluded that ATIM from MWP, RHA, and FA were excellent insulating components. The novel feature of the reported process is the development of non-toxic and asbestos-free thermal insulating low-cost material wherein chemically designed and mineralogically formulating desired phases lead to the homogeneous and effective thermal insulating matrix. The process is feasible, simple, cheap, and highly energy-efficient, increases production efficiency, and is environmentally friendly. The widespread use of advanced material for a broad application spectrum ranges from aerospace, automobile, electronics, transportation, construction, to other industries.
Keywords: Asbestos; Fly ash; Marble waste; Material; Rice husk ash; Thermal insulation

Tetraalkylammonium-based dicationic ionic liquids (ILs) for CO2 capture - Kulkarni, Prashant S.; Ranjane, Prathamesh; Mishra, Karun; Sundararajan, Swati; Kamble, Sanjay (New Journal of Chemistry, 2023)
This investigation includes the synthesis and characterization of a new series of ionic liquids (ILs) based on the tetraalkylammonium dication for the absorption of CO2, a step towards the development of more efficient and sustainable technologies. It was possible to synthesize amine-substituted PEG diacrylate by modifying poly(ethylene glycol) (PEG), which was then quaternized with 1-bromopentane to produce the IL PDBr. The other IL products, PDNTf2, PDBF4 and PDPF6, were synthesized via the metathesis of PDBr with the appropriate salt. The synthesized products were characterized using various techniques, such as FTIR, H-1 and C-13 NMR, elemental analysis, and density and viscosity meters, and evaluated as potential sorbents for CO2 capture. DSC and TGA were used to examine the thermal properties of the ILs. As observed from their thermal degradation behavior, the ILs exhibited two-stage disintegration with thermal stability up to 150 & DEG;C. The pressure drop method was used to study the sorption capacity of the ILs towards CO2. The sorption investigation showed that when the pressure is increased, the CO2 absorption increases. Equilibrium is reached in 40 minutes, demonstrating a rapid absorption rate. The IL with the [BF4](-) anion (PDBF4) demonstrated a maximum sorption capacity of 0.577 mole fraction of CO2, and can be regenerated and reused efficiently with less than 0.5% variation from its original absorption capacity. The CO2 absorption capacity for the ILs with other anions follows the trend: Br & AP; NTf2 < PF6 < BF4. This work shows that tetraalkylammonium-based dicationic ILs are adaptable, making them a suitable material for many applications, including sustainable CO2 capture technology.

Early detection of KP.2 SARS-CoV-2 variant using wastewater-based genomic surveillance in Pune, Maharashtra, India - Rajput, Vinay; Das, Rashmita; Pramanik, Rinka; Nannaware, Kiran; Sushma, Y.; Taji, Nyabom; Rajput, Vishal; Rajkhowa, Riyakshi; Pacharne, Poonam; Shah, Priyanki; Gogate, Niharika; Sangwar, Poornima; et al. (Journal of Travel Medicine, 2024)

Enhanced degradation of ciprofloxacin hydrochloride using hybrid advanced oxidation process of hydrodynamic cavitation and ozonation - Bodawar, Narendra; Shetty, Rohit; Kamble, Sanjay; Kulkarni, Prashant (Chemical Engineering & Technology, 2024)
The degradation of ciprofloxacin hydrochloride (CFX), an extensively utilized antibiotic for bacterial infections, has been studied through the application of advanced oxidation processes (AOPs) including hydrodynamic cavitation (HC), ozonation (O3), the Fenton reaction, chemical oxidation, and hybrid AOPs such as HC/O3 and Fenton/O3. Among these, the hybrid combination of HC/O3 demonstrated the highest CFX degradation of 99.82 % within 180 min having an initial concentration of 1000 ppm. The optimization of the HC/O3 process was conducted by varying parameters including initial concentration, pH, ozone (O3) gas flowrate, and temperature. Throughout the degradation process, CFX underwent intermediate formation, which gradually degraded over time. The hydrodynamic cavitation (HC) in combination with ozone, referred to as the HC/ozonation process, was used for the degradation of ciprofloxacin hydrochloride present in wastewater. This process underwent optimization with respect to various reaction parameters, including the initial concentration, ozone flow rate, pH level, temperature, the influence of ions, and the specific water matrix. At these optimized conditions a degradation efficiency of 99.82 % was achieved after 180 min. image
Keywords: active pharmaceutical ingredients; Advance Oxidation Processes; Ciprofloxacin hydrochloride; Hybrid AOPs; Hydrodynamic cavitation

Highly efficient, co-solvent assisted glycolytic depolymerization of waste polyethylene terephthalate (PET) into Bis(2-hydroxyethyl) terephthalate (BHET) monomer - Markandeya, Nishant; Solanki, Bhanupratap Singh; Ramalingam, Karthick; Kamble, Sanjay (Industrial & Engineering Chemistry Research, 2025)
Recently, growing use of plastics has led to the accumulation of waste that must be dealt with paramount priority. Among all plastic wastes, polyethylene terephthalate (PET) is the most widely used thermoplastic polyester globally because of its extensive applications in packaging, automotive manufacturing, and textile markets. Thus, there is a need to develop a sustainable and viable PET recycling process. This study presents an efficient solvothermal process for the depolymerization of PET into bis(2-hydroxyethyl) terephthalate (BHET) using co-solvent assisted glycolysis. The process uses N-methylimidazole (NMI) as a cosolvent with ethylene glycol (EG), achieving complete PET conversion and 92% BHET yield under optimized reaction conditions (180 degrees C, 45 min, PET:EG:NMI ratio of 1:7:8) without using a catalyst. The effectiveness of the cosolvent system was attributed to its polarity and H-bonding capabilities, which enhanced polymer swelling and facilitated the depolymerization. SEM analysis revealed pore formation in the NMI-treated PET, whereas FTIR studies confirmed the progressive formation of ester groups during depolymerization of PET. Kinetics studies based on different models indicated that, at higher temperatures, the surface reaction and homogeneous model proved to be rate-controlling due to the elimination of mass transfer limitations. A preliminary technoeconomic analysis and recyclability experiments further supported the scalability potential of the present study.

Magnetically separable Brønsted acid catalyst for the synthesis of Bisguaiacol-F - Tarade, Komal; Rode, Chandrashekhar; Kamble, Sanjay (New Journal of Chemistry, 2025)
Currently, polycarbonates, epoxy resins, and plastics are commercially made from Bisphenol-A. However, BPA-containing materials are well known for causing major health problems and have been banned in several countries. To address this concern, Bisguaiacol-F (BGF) has been developed as a safer and more sustainable alternative to Bisphenol-A. We created a novel sulfonic acid-functionalized, magnetically separable heterogeneous Br & oslash;nsted acid catalyst, [Fe3O4@SiO2-(Pr)3-N-Bu-SO3H][HSO4-], which was successfully utilized for the manufacture of BGF by condensing 37% aq. formaldehyde with two molecules of guaiacol. The main objective for this reaction was to avoid using excess guaiacol while also completing the conversion of both starting components. Surprisingly, our manufactured catalyst promotes the complete conversion of aqueous formaldehyde and guaiacol into regioisomers such as pp `-BGF, mp `-BGF and op `-BGF with 62%, 15%, and 6% selectivity, respectively. Our novel magnetically separable heterogeneous catalyst has improved catalytic activity in terms of starting material conversion and product distribution, which can be attributed to its unique structural characteristics. It contains a pendant -SO3H group that is connected to a lengthy butyl chain, making it conveniently accessible in the reaction. We have created the framework for a promising and environmentally aware approach to the synthesis of Bisguaiacol-F by meticulously optimizing reaction parameters such as time, temperature, reactant molar ratio, and catalyst loading. The catalyst was extensively characterized using acid-base titration, FT-IR, XRD, TGA, and NMR techniques to confirm the structure and reveal remarkable stability and activity. Notably, the catalyst demonstrated recyclability across six consecutive runs, with no noticeable reduction in its effectiveness. The catalytic activity was also tested for guaiacol condensation with a variety of aldehydes to create Bisguaiacol derivatives.

Monitoring influenza A (H1N1, H3N2), RSV, and SARS-CoV-2 using wastewater-based epidemiology: A 2-year longitudinal study in an Indian megacity covering omicron and post-omicron phases - Pramanik, Rinka; Nannaware, Kiran; Malik, Vinita; Shah, Priyanki; Sangewar, Poornima; Gogate, Niharika; Shashidhara, L. S.; Boargaonkar, Radhika; Patil, Dhawal; Kale, Saurabh; Bhalerao, Asim; Jain, Nidhi; et al. (Food and Environmental Virology, 2025)
{The bourgeoning field of wastewater-based epidemiology (WBE) for the surveillance of several respiratory viruses which includes Influenza A, H1N1pdm09, H3N2, respiratory syncytial viruses (RSV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is of interest for public health concerns. However, there are few long-term monitoring studies globally. In this study, respiratory viruses were detected and quantified from 11 sewer sheds by utilizing reverse transcription-quantitative polymerase chain reaction analysis in Pune city, India, from Jan 2022 to Dec 2023. The RNA fragments of respiratory viruses were detected in sewage samples before clinical cases were reported, underscoring the potential of WBE for early detection and monitoring within the population. The Spearman correlation of wastewater viral copies was positively and significantly correlated with the clinically positive case of H1N1pdm09 (rho = 0.55
Keywords: Influenza A; Quantitative reverse transcription-PCR; Respiratory viruses; SARS-CoV-2; Wastewater-based epidemiology

Solvent-assisted chemical recycling of polycarbonate using glycerol as a renewable chemical: mechanistic insights and statistical optimization - Markandeya, Nishant; Jadhav, Mayur; Gopale, Prafulla; Ramalingam, Karthick; Kamble, Sanjay (Process Safety and Environmental Protection, 2026)
The rapid accumulation of polycarbonate (PC) waste has driven the development of efficient recycling methods. This study presents a comprehensive investigation of solvent-assisted chemical recycling of PC using glycerol, a renewable chemical derived from industrial waste streams. Solvent screening highlighted the critical influence of solvent properties such as dielectric constant, dipole moment and hydrogen-bond accepting ability on depolymerization efficiency. A systematic approach combining Design of Experiments (DoE) and Response Surface Methodology (RSM) was employed to optimize the depolymerization process. Using a Box-Behnken design (BBD), the effects of key process parameters, including temperature, reaction time and the glycerol (GLY:PC) and dimethylformamide (DMF:PC) weight ratios, were evaluated in terms of PC conversion and bisphenol A (BPA) yield. The optimization model predicted that a reaction temperature of 171 degrees C, a reaction time of 1 h and a PC: GLY:DMF ratio of 1:5.05:7.22 would yield 100 % PC conversion and 85 % BPA yield. Experimental validation under these conditions achieved 100 % PC conversion and 83 % BPA yield, confirming the reliability of the model. Product characterization using NMR, LC-HRMS and FTIR confirmed the purity of BPA and provided insights into the reaction mechanism. The solvent recyclability across successive reaction cycles demonstrated the environmental and economic viability of the process. Overall, the energy demand calculation based on the environmental energy impact factor (xi) highlights the industrial relevance of this work and demonstrate an efficient and environmentally friendly catalyst-free route for depolymerization of polycarbonate with strong potential for industrial implementation.
Keywords: Chemical Recycling; Glycerol; Polycarbonate; Response surface methodology